ON THE ANALYSES OF THE PART OF SARAKHBORI ROST IN MAKOM ROST (Scientific journal of the Fergana State University, 2023)
This article is dedicated to the national art of Macom and presents the theoretical and  practical analyses of the structure, features of the melody and rhythm along with the text content of the Sarahbori Rost series from the vocal part of Rost in Shashmakom.